A CBT formulation of supervisees' narratives about unethical and harmful supervision. Issue 1 (2nd January 2017) - Reiser, Robert P.; Milne, Derek L.
ABSTRACT: There is growing evidence that clinical supervision may be experienced as harmful (Ellis et al., 2013). The 11 narrative accounts of supervision that form the focus of this Special Issue of The Clinical Supervisor corroborate this evidence, providing vivid and alarming accounts of supervisee experiences of unethical and harmful supervision. In order to treat these worrying reports of supervision with the seriousness that they deserve, we adopt a CBT formulation approach and apply it systematically to these narratives. First, we formulate the data contained in these narratives within a framework for judging unethical supervision. Then we develop proposed solutions to address the problems reported. Last, we describe practical implications for improvements in identifying and addressing unethical supervision and for minimizing harm to supervisees.